Participatory approaches for gender-sensitive research design - Kristjanson, Patricia M.; Ferdous, N.; Jost, Christine (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
The focus of climate-smart agriculture CSA) research is often on creating technological solutions to climate problems. Yet female and male farmers differ in terms of their vulnerability to climate change and the ways in which they benefit from technical interventions. We believe that targeting women with CSA practices, technology and information offers the greatest opportunity to increase the adaptive capacity of smallholder farming communities. This brief compiles some of the lessons learned while carrying out participatory action research activities and methodologies.